Age-associated epigenetic drift trajectory and cross-national disparities in accelerated aging in domestic dogs - Subin Jang; Seong Jun Kim; Dayeon Kang; Chae-yeon Hong; Eun-yeong Bok; Sung-Lim Lee; Yong-Ho Choe; Jaemin Kim (Proceedings of the National Academy of Sciences, 2026)
Aging is accompanied by both increasing interindividual heterogeneity and systematic, age-associated alterations in DNA methylation (DNAm). Here, we investigated these complementary dimensions of epigenetic aging in dogs using global and locus-specific measures of epigenetic drift alongside clock-based estimates of biological aging. We observed pervasive, yet genomically structured epigenetic instability throughout the canine lifespan. The extent of age-associated epigenetic drift further varied by body size, suggesting biological stratification of methylation instability. Cross-national comparison of clock-derived epigenetic age acceleration (EAA) between South Korea and the United States revealed consistently higher EAA in Korean dogs, with sex-associated differences detected within the Korean cohort. We further identified CpGs with cohort-specific age-associated methylation patterns, indicating that population-level differences in epigenetic aging extend beyond clock-based estimates to locus-specific methylation dynamics. Together, these findings highlight population-level diversity in canine epigenetic aging and support dogs as a tractable model for investigating biological and environmental determinants of age-related epigenetic change.